Effects of Electroconvulsive Therapy on Depression and Its Potential Mechanism - Li, Ming; Yao, Xiaoxiao; Sun, Lihua; Zhao, Lihong; Xu, Wenbo; Zhao, Haisheng; Zhao, Fangyi; Zou, Xiaohan; Cheng, Ziqian; Li, Bingjin; Yang, Wei; Cui, Ranji (Frontiers in Psychology, 2020)
Depression is one of the most common disorders causing mortality around the world. Although electroconvulsive therapy (ECT) is, with antidepressants and psychotherapy, one of the three major treatments of depression, it is still considered the last resort for depressed patients. This situation is partially due to limited studies and uncertainty regarding its mechanism. However, decades of increased research have focused on the effects of ECT on depression and its potential mechanism. Furthermore, these investigations may suggest that ECT should be a first-line therapy for depression due to its profound effects in relieving desperation in certain situations. Here we outline recent clinical and preclinical studies and summarize the advantages and disadvantages of ECT. Thus, this review may provide some hints for clinical application.